A Hypertensive Response to Exercise Is Prominent in Patients With Obstructive Sleep Apnea and Hypertension: A Controlled Study. Issue 7 (29th April 2013) - Kasiakogias, Alexandros; Tsioufis, Costas; Thomopoulos, Costas; Andrikou, Ioannis; Kefala, Anna; Papadopoulos, Dimitrios; Dima, Ioanna; Milkas, Anastasios; Kokkinos, Peter; Stefanadis, Christodoulos
<x xml:space="preserve">Abstract</x> Blood pressure (BP) behavior during exercise is not clear in hypertensive patients with obstructive sleep apnea (OSA). The authors studied 57 men with newly diagnosed essential hypertension and untreated OSA (apnea‐hypopnea index [AHI] ≥5) but without daytime sleepiness (Epworth Sleepiness Scale score ≤10), and an equal number of hypertensive controls without OSA matched for age, body mass index, and office systolic BP. All patients underwent ambulatory BP measurements, transthoracic echocardiography, and exercise treadmill testing according to the Bruce protocol. A hypertensive response to exercise (HRE) was defined as peak systolic BP ≥210 mm Hg. Patients with OSA and control patients had similar ambulatory and resting BP, ejection fraction, and left ventricular mass. Peak systolic BP was significantly higher in patients with OSA (197.6±25.6 mm Hg vs 187.8±23.6 mm Hg; P=.03), while peak diastolic BP and heart rate did not differ between groups. Furthermore, an HRE was more prevalent in patients with OSA (44% vs 19%; P=.009). Multiple logistic regression revealed that an HRE is independently predicted by both the logAHI and minimum oxygen saturation during sleep (odds ratio, 3.94; confidence interval, 1.69–9.18; P=.001 and odds ratio, 0.94; confidence interval, 0.89–0.99; P=.02, respectively). Exaggerated BP response is more prevalent in nonsleepy hypertensives with OSA compared with their nonapneic counterparts. This finding may have distinct diagnostic and prognostic implications.